Using Practice-Based Coaching to Increase Use of Language Facilitation Strategies in Early Head Start and Community Partners. Issue 3 (July 2018) - Donegan-Ritter, Mary; Van Meeteren, Beth
Abstract : This article describes how practice-based coaching was used with Early Head Start infant and toddler teachers to support their use of evidence-based language facilitation strategies. Video-based self-reflection and focused feedback allowed teachers to recognize what they were already doing well and increased the fidelity of evidence-based practices. Observational data show changes that took place over the course of the 3 monthly coaching cycles and 6-month follow-up. Teachers increased their use of encouraging back-and-forth exchanges and parallel talk to varying extents. Goal setting was associated with infant–toddler teachers increasing their use of specific strategies. Coach use of nonjudgmental "I notice" statements contributed to a safe and supportive experience. In this pilot study, infant–toddler teachers benefitted from video-based self-reflection and coaching to transfer the use of language facilitation strategies. Focusing on teacher strengths and creating opportunities for skill development through goal setting, individualized support and performance-based feedback facilitated the use of language facilitation strategies in infant–toddler care settings.